Advertising and the end of the world - Jhally, Sut; Media Education Foundation (Northampton, Mass. : Media Education Foundation, 1998)
Extensively illustrated with graphics and examples from commercial imagery, Advertising and the End of the World presents a compelling and accessible argument about consumerism and its impact on the earth's future
Title from title screen
Writer and editor, Sut Jhally ; camera & graphics, Sanjay Talreja ; original music, Thom Monahan
With English and Spanish subtitles
Keywords: Advertising -- Social aspects -- United States; Advertising -- Psychological aspects -- United States; Popular culture -- United States; Communication in marketing